PENGGUNAAN EVALUASI WHEEL MODEL DALAM KEGIATAN OUTING CLASS UNTUK MENINGKATKAN CAPAIAN PEMBELAJARAN NILAI AGAMA DAN MORAL ANAK DI TK AISYIYAH AL AMIN SURAKARTA - Sugiyanti; Ari Anshori (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The teaching of religious and moral values is closelyrelated to a child's character, polite behavior, and willingness topractice religious teachings in daily life. The evaluation of the wheel model in outing class activities has the potential to significantly improve learning outcomes, especially in integrating the aspects of teaching religious and moral values. This study aims to examine in depth the use of the wheel model evaluation in outing class activitiesto improve children's religious and moral learning outcomes. The research methodused is a literature study. The results of the study indicate that the use of the wheel model evaluation in outing class activities provides a strong and flexible framework that significantly improves learning outcomes. Its success is highly dependent oncareful implementation, adequate planning, and the integration of assessment methodsthat are in line with the objectives of the activities outside the classroom.